2020
DOI: 10.2147/ijn.s220057
|View full text |Cite
|
Sign up to set email alerts
|

<p>Efficient miRNA Inhibitor Delivery with Graphene Oxide-Polyethylenimine to Inhibit Oral Squamous Cell Carcinoma</p>

Abstract: Background: MicroRNAs (miRNAs) are widely believed to be promising targets for oral squamous cell carcinoma (OSCC) gene therapy. miR-214 has been identified as a promoter of OSCC aggression and metastasis. Methods: Graphene oxide-polyethylenimine (GO-PEI) complexes were prepared and loaded with a miRNA inhibitor at different N/P ratios. The transfection efficiency of GO-PEI-inhibitor was tested in Cal27 and SCC9 cells. Moreover, the tumor inhibition ability of GO-PEI-inhibitor was measured in an OSCC xenograft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Furthermore, the terminal can also link with GBNs through surface functionalization to change the physical and chemical properties, reactivity, kinetics, and biological properties. A previous study reported that GO-PEI complexes encapsulate miR-214 inhibitors for the treatment of oral squamous cell carcinoma . GO modified by PAMAM dendrimers has a strong affinity to human breast cancer cell membrane and has no significant cytotoxicity .…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Furthermore, the terminal can also link with GBNs through surface functionalization to change the physical and chemical properties, reactivity, kinetics, and biological properties. A previous study reported that GO-PEI complexes encapsulate miR-214 inhibitors for the treatment of oral squamous cell carcinoma . GO modified by PAMAM dendrimers has a strong affinity to human breast cancer cell membrane and has no significant cytotoxicity .…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…According to the analysis of differential expression genes in OSCC, we found that these genes are tightly correlated with p53 signaling pathway [ 32 ],which could regulate cell proliferation, apoptosis and autophagy [ 33 , 34 ]. Furthermore, the OSCC cell apoptotic levels could be significantly inhibited through targeting p53 [ 35 ]. Increased levels of p53 in the cytoplasm are involved in inhibiting autophagy [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Electrostatic repulsion exists between GO and nucleic acid because they are both negatively charged, while polyetherimide (PEI) is a positively charged gene vector with a proton sponge effect, which can reduce the electrostatic repulsion between miRNAs and GO, thus improving the overall stability 61 . Ou et al firstly reported a gene therapy strategy for OSCC treatment by using positively charged PEI-functionalized GO to transport the inhibitor of miR-214 for suppressing OSCC cell proliferation 25 . In vitro and in vivo results showed that this nanocarrier could remarkably inhibit Cal27 and SCC9 tumor cell growth and migration by targeting phosphatase and tensin homolog (PTEN) and p53.…”
Section: Carbon Nanomaterials For Cancer Treatmentmentioning
confidence: 99%